HEMOGLOBIN AND HEMATOCRITE CHANGES DURING UNCOMPLICATED ANESTHESIA: GENERAL ANESTHESIA AND LOCAL ANESTHESIA - KH NAGHIBI (Journal of Research in Medical Sciences, 2002)
Introduction. Despite of vital role of blood and it"s components as an only curable treatment, it"s transfusion is accompanied by many complications. In the other way, the most important adverse effects of anemia is decrease in oxygen supply to the tissues. Therefore, it is essential to determine those patients need to blood transfusion and exact hemoglobine and hematocrite level which transfusion become necessary. Recent studies show that during general anesthesia due to vasodilation in the level of microcirculation and passage of many red blood cells from microcirculation there is a decreasing in hemoglobine level measured in peripheral veins which named plasma skimming. So, during sampling of hemoglobine and hematocrite from peripheral veins, there is a pseudodecrease in Hb and HCT levels. In this study we want to determine this decrease in Hb and HeT.
Methods. Study was done in 182 patients with ASA 1 and 2 undergoing general or local anesthesia for cataract surgery. Duration of nill per os (NPO), preoperotive and intraoperative intravenous fluid administration were simillar in two groups. A sample of blood for preoperative evaluation and another one immediately after operation achevied and compared with each other.
Results. There was not significant differences between mean Hb and HCT in two groups preoperotive. But postoperative, there was a significant differences between mean Hb and HCT in general anesthesia vs local anesthesia (P < 0.01). This decrease in Hb and HCT was orderly 0.91 ± 1.14 gr/dl for Hb and 2.862±3.6 percent for Hct.
Discussion. In determining of Hb and HCT immediately after general anesthesia, there is some pseudo decrease due to plasma skimming that must be appreciated.